Morphemic Composition of the Word and the Importance and Functions of Working on Word-Building - Adizova Nigora Bakhtiyorovna; Ergashova Dilsora (Research Parks Publishers, 2021)
In this article, it is mentioned about the methods and techniques of teaching the components of the word: the core and the suffixes to the pupils of the primary classes in order to study the components of the words in the Uzbek language, that is, the meaningful parts, as well as to inform the pupils of the primary classes about this phenomenon.